2015
DOI: 10.1055/s-0035-1546006
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of Aqueous Infusions of Artemisia herba-alba and Ajuga iva in Alloxan-Induced Diabetic Rats

Abstract: The aqueous infusions of the aerial parts of Artemisia herba-alba Asso and Ajuga iva Schreber, prepared in accordance with the traditional procedure used in the local folk medicine, have been analysed for their composition and content of phytochemical constituents and examined for their antidiabetic effectiveness in alloxan-induced diabetic rats. Oral administration of A. herba-alba and A. iva infusions was studied in normal and alloxan-induced diabetic rats, which were randomly divided into nine groups, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Furthermore, our findings are in line with previous studies that have proven that some medicinal plants have more potent inhibitory activities than the reference compound such as acarbose 37,38 . Moreover, our results are in agreement with other studies that found that the aqueous extract of A iva decreased blood glucose levels in diabetic rats compared to the control group 39,40 . Furthermore, our study showed similar results with a recent work 21 that evaluated the antidiabetic effect of A iva extracts on the same enzymes.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, our findings are in line with previous studies that have proven that some medicinal plants have more potent inhibitory activities than the reference compound such as acarbose 37,38 . Moreover, our results are in agreement with other studies that found that the aqueous extract of A iva decreased blood glucose levels in diabetic rats compared to the control group 39,40 . Furthermore, our study showed similar results with a recent work 21 that evaluated the antidiabetic effect of A iva extracts on the same enzymes.…”
Section: Resultssupporting
confidence: 93%
“…It was well confirmed after oral administration of A. herba-alba and A. iva infusions in normal and alloxan-induced diabetic rats. [7] Similar antidiabetic activity was reported in Alstonia scholaris (L.) R. Br., Blumea balsamifera (L.) DC., Cinnamomum burmanni Nees ex Bl., and Piper betle L. [8] Although there are so many possibilities to control increasing glucose level, improvement of β-cell function and insulin secretion in pancreatic cells can induce utilization of external glucose.…”
Section: Therapeutic Approachessupporting
confidence: 70%
“…Luisa, et al & Cazarolli, et al [16] have shown that the apigenin-6-C-β-fucopyranoside from Averrhoa carambola possess an antihyperglycemic activity. Similarly, Boudjelal, et al [17] have reported that apigenin reduced the glucose level in alloxan induced rats. Many reports have shown that chrysin possesses antihyperglycemic activity [16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 84%
“…Similarly, Boudjelal, et al [17] have reported that apigenin reduced the glucose level in alloxan induced rats. Many reports have shown that chrysin possesses antihyperglycemic activity [16][17][18][19][20][21][22]. These finding provide convincing evidence that the effect of the PB aqueous extract in reducing the glucose level is due to the presence of apigenin 6c-glucoside and chrysin.…”
Section: Resultsmentioning
confidence: 84%